Room-temperature fabrication of multi-deformable perovskite solar cells made in a three-dimensional gel framework. Issue 86 (1st September 2016) - Ma, Mingming; Tang, Qunwei; Yang, Peizhi; He, Benlin
Abstract : Ultraflexible perovskite solar cells are made by absorbing solar cell materials into 3D gel framework, yielding enhanced photovoltaic performances under deformations. Abstract : Application-specific requirements for future perovskite solar cells (PSCs) include being lightweight, having mechanical resilience, and deformability for multi-purpose utilizations ranging from electronic skins and implants in the body to wearable textiles. In the current work, multi-deformable PSCs were made by imbibing solutions with polyaniline, solvothermal-processed (l -Lys)0.038 (CH3 NH3 )0.962 PbI3 precursor and electron-transporting PCBM in the 3D framework of an amphiphilic PAA–PEG gel matrix. Subsequently, after the solvent removal steps, PSCs with enhanced cell efficiencies and excellent durability under repeated deformations and moisture attack are yielded.